PENGARUH PERKEMBANGAN TEKNOLOGI INFORMASI, PENGETAHUAN INVESTASI, DAN PENDAPATAN TERHADAP MINAT INVESTASI SAHAM GENERASI MUDA DI PASAR MODAL - Nugroho, Mahfud (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
This research aims to determine the influence of advances in information technology (X1), investment knowledge (X2), and income (X3) on interest investment in stock (Y) in the millennial generation. The population is millennials who have attended both formal and non-formal training regarding investment in the capital market. The number of samples in this study was 104 people. Determining the sample used a purposive sampling technique. The research results found that technological developments and income had a positive and significant influence on the millennial generation's stock investment interest. Meanwhile, investment knowledge has a positive influence but not significant influence on the millennial generation's stock investment interest in the capital market.